Struktur Pertunjukan Wayang Kulit Jum’at Kliwonan Taman Budaya Surakarta - Harijadi Tri Putranto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
The Purwa Wayang Kulit Performing Friday Kliwonan program has been pioneered since 1984, beginning with the thought of the Central Java Cultural Park in Surakarta as an umbrella and protector of art that is expected to provide opportunities for the next generation of art. In general, puppeteers who appear present the arable story by referring to the plays that are commonly performed by previous puppeteers. The study results show, that in the era of 2004 to 2009 there were three scenes structure of wayang kulit performances last night, namely the structure of scenes that still refers to old patterns, the structure of scenes that refer to the work of solid engraving does not follow the pathet pattern, and the structure of scenes that are not referring to the reverse flow and not necessarily in sequence with the play. Keywords: Puppet show, Friday Kliwon, Taman Budaya, Surakarta.